For the church community after COVID-19 - Cho, Anna (Dialog, 2021)
COVID-19 is changing everyday life. COVID-19 is also changing the look of the church. The church is a community of people who gather for worship, fellowship, and sharing. However, due to the coronavirus, the church is no longer able to gather and worship together. Moreover, because of the coronavirus, social distancing with as little as possible face-to-face contact has been recommended worldwide. If this situation is prolonged, the church community interactions will have difficulty in surviving. Therefore, this article seeks ways to maintain and strengthen the church community in and after the coronavirus era through insight into speech act theory.